2014
DOI: 10.1111/jam.12593
|View full text |Cite
|
Sign up to set email alerts
|

Biogeochemical activity of microbial biofilms in the water column overlying uranium mine tailings

Abstract: This study demonstrates the biogeochemical potential of microbial biofilm communities in the water column covering an alkaline uranium tailings body; specifically, the nature of the bacterial groups detected (Aquabacterium, Dechloromonas) and the presence of reduced iron suggest that complex hydrocarbons are available for bacterial growth and geochemical change, such as iron reduction, can occur even though the system bulk phase is predominantly oxic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 66 publications
(183 reference statements)
0
4
0
Order By: Relevance
“…For example, we found a high relative abundance of Aquabacterium ( Figure 4 , ASV 17033, Betaproteobacteriales, Gammaproteobacteria) in the entire water column of the western subtropical Pacific Ocean. Bondici et al (2014) found the nature of Aquabacterium detected in the water column and the presence of reduced iron suggested that complex hydrocarbons were available for their growth and geochemical change, such as iron reduction. These observations raise questions on their adaptation to the marine environments they inhabit and the ecological functions they probably perform.…”
Section: Discussionmentioning
confidence: 99%
“…For example, we found a high relative abundance of Aquabacterium ( Figure 4 , ASV 17033, Betaproteobacteriales, Gammaproteobacteria) in the entire water column of the western subtropical Pacific Ocean. Bondici et al (2014) found the nature of Aquabacterium detected in the water column and the presence of reduced iron suggested that complex hydrocarbons were available for their growth and geochemical change, such as iron reduction. These observations raise questions on their adaptation to the marine environments they inhabit and the ecological functions they probably perform.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies of the microbial response to AgNPs have been conducted with planktonic cells, , even though bacteria in the environment commonly attach to surfaces and form biofilms . Whereas biofilms can beneficially participate in biogeochemical cycles, waste degradation, and clean energy generation, they are also implicated in biofouling, biocorrosion, pathogenic infection, and disease outbreaks. Thus, prevention of biofilm formation is one objective of incorporating AgNPs on material surfaces. ,, …”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the relatively significant genus in the inoculated sludge was Candidatus , while the dominant micro‐organisms in sample FS2 changed into the denitrificating bacteria of genera Hydrogenophaga and Dechloromonas , due to enrichment cultivation (Achenbach et al, 2001; Bondici et al, 2014). Besides, the relative abundances of the genera Thauera , Azospirillum and Hyphomicrobium in the biofilm significantly increased as compared with those in the inoculated sludge, all of which are closely related to denitrification function (Chowdhury et al, 2007; Pacovsky, 1990; Zhang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%